TRUST AND COOPERATION RELATIONS IN ENVIRONMENTAL MANAGEMENT OF LEBANON - Abbas, Nivine H.; van der Molen, Irna; Nader, Manal R.; Lovett, Jon C. (European Scientific Journal, ESJ, 2014)
This paper investigates trust and cooperation in the context of environmental management in Lebanon. Literature already indicated increasing environmental problems in this area that suffered from repeated episodes of armed conflict. The Lebanese government has been faced by many difficulties to address these environmental challenges. While ‘trust’ and ‘cooperation’ are referred to in literature as two of these problems, these are not systematically studied in the case of Lebanon. We assume that there is a relation between trust and cooperation. The more there is trust relations, the more there will be cooperation and vice versa. The findings are based on structured and semi-structured interviews with public and private stakeholders, survey with citizens in northern Lebanon, and collection of secondary sources. Results show that citizens have lack of trust in the stakeholders of the public sector at national level (96.1%) and there is low level of citizens’ participation in the environmental initiatives. Furthermore, stakeholders in the public and private sector indicate that cooperation between public and private sectors in addressing environmental problems is relatively weak and that trust is one of the factors that are leading to this. At the same time, however, literature and primary data indicate that some of these stakeholders involved successfully circumvent environmental regulations by using “wasta” that is their relations of trust and cooperation with public authorities. In Lebanon, we therefore have to distinguish between trust and cooperation as a means to hinder environmental management, and trust and cooperation as a means to enhance environmental management.